Comparison of multiplex-serology and ELISA based methods in detecting HPV16 L1 antibody responses in paired saliva and serum samples of healthy men - Vuokko Loimaranta; Karoliina Sievi; Jill Werner; Michael Pawlita; Tim Waterboer; Julia Butt; Stina Syrjänen (Elsevier B.V., 2022)
Human papilloma viruses (HPV) are a common cause of transient infections on mucosal surfaces, also in the oral cavity. Some infections remain persistent and can, especially with high risk HPV genotypes, lead to malignancies in the oral-oropharyngeal area. Our understanding of the natural course of oral HPV infections is limited, and the local host responses are poorly known. In this study we show that anti-HPV16L1 antibodies, the IgA response being most abundant, can be measured in saliva of asymptomatic males. HPV16L1 specific multiplex serology and commercial ELISA methods were compared and also the total salivary IgA levels measured. The total salivary IgA concentrations varied from 36 to 163 μg/ml. All the assays could detect anti-HPV16 IgA from saliva, but the correlation between assays varied from non-significant 0.22 to highly significant 0.81, p < 0.01. Salivary antibody responses did not correlate with the antibody responses detected in serum (Spearman correlations between −0.12 and 0.16) not even after adjusting the specific responses to differences in total IgA in saliva. Only six of 34 individuals were HPV16 DNA positive at the time of the sampling, but interestingly, three out of four with oral HPV16 DNA had salivary anti-HPV16 IgA responses below average. In conclusion, our results show that anti-HPV16 antibodies can be measured from saliva and the salivary response differs from that of serum. Individual differences in total salivary antibody concentrations may affect also the amount of HPV16 specific antibodies in saliva. Furthermore, different assay methods showed different specificities; thus comparisons between studies must be done with care.